Frugal Living, Digital Financial Literacy, and Sustainable Wealth: The Moderating Role of Financial Management Behavior - Nadia Dwi Irmadiani; Ari Pradhanawati; Reni Shinta Dewi (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose: This study examines the effects of frugal living and digital financial literacy on sustainable wealth, with financial management behavior as a moderating variable. It also compares the proposed relationships across different household employment groups. Design/methodology/approach: A quantitative approach was employed using Covariance-Based Structural Equation Modeling with Maximum Likelihood estimation. Data were collected through an online questionnaire from 253 married mothers who had at least one child and actively used digital financial services. Multi-group analysis was conducted to compare working mothers and stay-at-home mothers. Findings/Results: Frugal living has a positive and significant effect on sustainable wealth, as does digital financial literacy. Financial management behavior moderates the relationships between these two factors and sustainable wealth. The multi-group analysis also indicates a significant difference in the structural relationships between working mothers and stay-at-home mothers. Originality/Value: This study integrates frugal living, digital financial literacy, and financial management behavior within a sustainable wealth framework. The findings highlight the need for differentiated financial education programs that strengthen prudent consumption, digital financial competence, and household financial management practices.